Novel ACT-based eHealth psychoeducational intervention for students with mental distress: a study protocol for a mixed-methodology pilot trial. Issue 7 (16th July 2019) - Edwards, Darren J; Rainey, Elinor; Boukouvala, Vasiliki; Wells, Yasmin; Bennett, Paul; Tree, Jeremy; Kemp, Andrew H
Abstract : Introduction: Recent studies have revealed a high prevalence of depression, anxiety and stress symptoms among university students, highlighting an urgent need for preventative measures at low cost to better support often overwhelmed support services. Objective: Here we propose a protocol for assessing the feasibility of a randomised controlled trial (RCT) for an online transdiagnostic psychoeducational intervention called 'A Bite of ACT' compared with a waitlist control. Methods and analysis: This is an RCT with crossover design involving baseline assessments and two follow-up periods. The primary outcome measure will be the Acceptance Checklist for Clinical Effectiveness Pilot Trials (ACCEPT) for measuring the feasibility of the trial design and methods. Secondary outcomes include measures of well-being, social connectedness, quality of life (EuroQol Five Dimensions), depression, anxiety and stress (Depression Anxiety Stress Scales-21), as well as the process measures: psychological flexibility (Acceptance and Action Questionnaire-Second Version and the Mindful Attention Awareness Scale) and heart rate variability. Analysis will involve calculating descriptive statistics, examining trial feasibility outcomes through ACCEPT, and determining effect size measures to determine the sample size needed in a future trial (if indicated). Qualitative interviews and preliminary health economics analysis will provide additional insights into the feasibility of the intervention and trial methods. Ethics and dissemination: This study has been approved by the Department of Psychology Research Ethics Committee in the College of Human and Health Sciences at Swansea University. Dissemination will involve publication in international peer-reviewed journals, presentation of findings at relevant local, national and international conferences, and promotion of study outcomes using social media and other channels for disseminating findings to the wider community. Trial registration number: NCT03810131 ; Pre-results.